Sub-surface constructed wetlands for pesticides removal by using vetiver grasses - Chan, Hong Lup (2012)
Water pollution is one of the phenomenons that occurred normally nowadays. It has become serious problem and gives bad impacts on human health, aquatic lives and environmental. An ecological technology approach has been developed involving the use of plants to clean up or remediate soils and water contaminated with toxic chemical substance which is the Phytoremediation process. The objective of this project is to study and evaluate the contaminated water remediation using phytoremediation process and also to identify the effectiveness of Vetiver sp as a plant in phytoremediation. In this study, Vetiver sp (Vetiveria Zizanoides) was used to identify the effectiveness of uptake of chemical contaminant. Vetiver grass has a fast and high capacity for absorption of nutrients, particularly nitrogen and phosphorus in wastewater. The scope of study is the pesticide-water mix sample as influent and the laboratory test will be carried out for the effluent water sample. In methodology, total volume of 50Liter of influent water sample were prepared with the ratio of 1: 1OOO(pesticide, tap water) and stored inside the PVC water tank. The influent water sample was flow into three type of constructed wetland which is the filled with vetiver grass, vetiver grass and limestone, without vetiver grass condition. The treatment process is run for five day and the treated effluent sample was taken once for each day for the water quality analysis. The water quality parameter of the effluent water was measured such as pH value (pH), Chemical Oxygen Demand (COD), Total Suspended Solids (TSS), Orthophosphate, and Nitrate. From the results, the percentage of removal obtained from the effluent result of CW with vetiver grass is pH 4.85%, TSS 89.53%, COD 42.91 %, Nitrate 67.86%, and Orthophosphate 22.25%. However, the findings that percentage of removal obtained from the effluent result of CW with vetiver grass and limestone are pH 5.52%, TSS 91.31%, COD 59.27%, Nitrate 59.38%, and Orthophosphate 26.72%. In conclusion, the vetiver grass is potential to reduce the pesticides in the water.